2022
DOI: 10.3389/fnins.2022.982829
|View full text |Cite
|
Sign up to set email alerts
|

Myelin damage and cortical atrophy in watershed regions in patients with moyamoya angiopathy

Abstract: BackgroundDespite it being known that chronic ischemia results in myelin damage and gray matter atrophy, data regarding patients with moyamoya angiopathy is limited. We hypothesized that chronic ischemia in moyamoya angiopathy leads to myelin damage, especially in anterior watershed regions, as well as cortical atrophy in these areas.Materials and methodsTwenty adult patients with moyamoya angiopathy and 17 age- and sex-matched healthy controls were evaluated using the T1w/T2w mapping method and surface-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Several studies have revealed myelin damage due to hypoperfusion within the hemispheric white matter in patients with MMA [28,29]. It is unclear, however, whether these changes are reversible [18,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have revealed myelin damage due to hypoperfusion within the hemispheric white matter in patients with MMA [28,29]. It is unclear, however, whether these changes are reversible [18,29].…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a few studies dedicated to white matter perfusion changes in patients with MMA have been published [17]. However, white matter watershed regions (such as the semiovale center) are the most prone to chronic ischemic changes in MMA [18], and it is still unclear what changes can be found in these patients after bypass surgery. Thus, the purpose of this study was to estimate cerebral hemodynamic changes in gray matter and white matter in children with MMA after revascularization surgery.…”
Section: Introductionmentioning
confidence: 99%